2021
DOI: 10.31101/jitu.2015
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Short Foot Excercisedan Tibialis Posterior Strengthening Terhadap Keseimbangan Dinamis Pada Penderita Flat Foot Remaja Narrative Review

Abstract: Masalah kesehatan usia remaja merupakan salah satu masalah penting dalamsiklus kehidupan.Salah satu dari berbagai masalah kesehatan remaja ialah gangguan muskuloskeletal berupa kelainan bentuk telapak kaki (flexible flat foot).Dampak yang akan terjadi akibat flat foot yaitu nyeri, mudah lelah bila berjalan jauh, sepatu cepat halus, perubahan biomekanik tubuh yang akan menyebabkan gangguan keseimbangan, gangguan berjalan serta deformitas yang memudahkan terjadinya cedera. Cedera pada remaja dapat menurunkan pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This stretching is also widely practiced in swimming athletes, both dynamically and statically in an effort to increase joint space (Susanto, 2010), to improve dynamic balance to minimize the risk of injury there are short leg training interventions and posterior tibialis strengthening (Haq & Imania, 2021), further research evidence states that stretching has a relationship with vertical jump performance and 60 meter running (Apriantono et al, 2020). It is concluded that to improve dynamic balance to prevent injury there is an intervention of short leg training and posterior tibialis strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…This stretching is also widely practiced in swimming athletes, both dynamically and statically in an effort to increase joint space (Susanto, 2010), to improve dynamic balance to minimize the risk of injury there are short leg training interventions and posterior tibialis strengthening (Haq & Imania, 2021), further research evidence states that stretching has a relationship with vertical jump performance and 60 meter running (Apriantono et al, 2020). It is concluded that to improve dynamic balance to prevent injury there is an intervention of short leg training and posterior tibialis strengthening.…”
Section: Discussionmentioning
confidence: 99%